An enzyme-linked immunosorbent assay for detecting the chicken B cells - Benda, V; Angelisová, P; Jandlová, T; Mach, O; Slezáková, P (Folia biologica, 1986)
Two modifications of an indirect enzyme immunoassay described here allow the discernment of chicken B and T cells when a polyclonal rabbit anti-chicken Ig antibody or a monoclonal antibody reactive with chicken IgM and IgG heavy chains is used. Comparison of both types of antibody in ELISA and in indirect immunofluorescence suggests that they can readily be exploited for detection of lymphoid cells with surface immunoglobulin markers.
Keywords: imunoglobulin M; imunoglobulin G; T-Lymphocytes; Chickens; Fluorescent Antibody Technique; B-Lymphocytes; fluorescenční protilátková technika; T-lymfocyty; Immunoglobulin G; ELISA; Enzyme-Linked Immunosorbent Assay; Immunoglobulin M; zvířata; kur domácí; Animals; monoklonální protilátky; B-lymfocyty; Antibodies, Monoclonal